Associations between active travel to work and overweight, hypertension, and diabetes in India: a cross-sectional study. - Christopher Millett (Public Library of Science (PLoS), 2013)
Background Increasing active travel (walking, bicycling, and public transport) is promoted as a key strategy to increase physical activity and reduce the growing burden of noncommunicable diseases (NCDs) globally. Little is known about patterns of active travel or associated cardiovascular health benefits in low- and middle-income countries. This study examines mode and duration of travel to work in rural and urban India and associations between active travel and overweight, hypertension, and diabetes. Methods and findings Cross-sectional study of 3,902 participants (1,366 rural, 2,536 urban) in the Indian Migration Study. Associations between mode and duration of active travel and cardiovascular risk factors were assessed using random-effect logistic regression models adjusting for age, sex, caste, standard of living, occupation, factory location, leisure time physical activity, daily fat intake, smoking status, and alcohol use. Rural dwellers were significantly more likely to bicycle (68.3% versus 15.9%; p<0.001) to work than urban dwellers. The prevalence of overweight or obesity was 50.0%, 37.6%, 24.2%, 24.9%; hypertension was 17.7%, 11.8%, 6.5%, 9.8%; and diabetes was 10.8%, 7.4%, 3.8%, 7.3% in participants who travelled to work by private transport, public transport, bicycling, and walking, respectively. In the adjusted analysis, those walking (adjusted risk ratio [ARR] 0.72; 95% CI 0.58-0.88) or bicycling to work (ARR 0.66; 95% CI 0.55-0.77) were significantly less likely to be overweight or obese than those travelling by private transport. Those bicycling to work were significantly less likely to have hypertension (ARR 0.51; 95% CI 0.36-0.71) or diabetes (ARR 0.65; 95% CI 0.44-0.95). There was evidence of a dose-response relationship between duration of bicycling to work and being overweight, having hypertension or diabetes. The main limitation of the study is the cross-sectional design, which limits causal inference for the associations found. Conclusions Walking and bicycling to work was associated with reduced cardiovascular risk in the Indian population. Efforts to increase active travel in urban areas and halt declines in rural areas should be integral to strategies to maintain healthy weight and prevent NCDs in India. Please see later in the article for the Editors' Summary.